Anting-anting o kung bakit nagtatago sa loob ng bato si bathala - Pambid, Nenita Deapera 1955- ([Quezon City] University of the Philippines Press, 2000)
Filipino beliefs in using amulet to bring good luck and to avert evil.
Includes bibliographical references and index.
In Tagalog.
Keywords: Amulets -- Philippines; Philippines -- Religion